A Primer on Genetic Testing for Horse Owners and Breeders : VM261, 4/2024 - Ciosek, Julia; Wickens, Carissa; Brooks, Samantha A. (EDIS, 2024)
With the increasing development of genetic testing and advanced genomic technologies, horse owners and breeders have more opportunities than ever before to learn more about the genetic background of their horses. This publication provides information to help horse owners and breeders understand what genetic testing services are, which genetic tests are available for their horses, and how to locate genetic testing services. Written by Julia L. Ciosek, Carissa Wickens, and Samantha A. Brooks, and published by the Veterinary Medicine—Department of Large Animal Clinical Sciences, UF/IFAS Extension, April 2024.